CMOS and beyond : logic switches for terascale integrated circuits - Liu, Tsu-Jae King; Kuhn, Kelin (Cambridge : Cambridge University Press, 2014)
Get up to speed with the future of logic switch design with this indispensable overview of the most promising successors to modern CMOS transistors. Learn how to overcome existing design challenges using novel device concepts, presented using an in-depth, accessible, tutorial-style approach. Drawing on the expertise of leading researchers from both industry and academia, and including insightful contributions from the developers of many of these alternative logic devices, new concepts are introduced and discussed from a range of different viewpoints, covering all the necessary theoretical background and developmental context. Covering cutting-edge developments with the potential to overcome existing limitations on transistor performance, such as tunneling field-effect transistors (TFETs), alternative charge-based devices, spin-based devices, and more exotic approaches, this is essential reading for academic researchers, professional engineers, and graduate students working with semiconductor devices and technology.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Metal oxide semiconductors, Complementary; Integrated circuits